Evidence of Non-Linear Relationship between Non-Interest Income and Profitability of Commercial Banks in Pakistan - Noor, Iraj; Siddiqui, Danish Ahmed (Asian Journal of Economic Modelling, 2019)
Pakistan’s commercial banks are lately facing hindrance in earning substantial profits due to low-interest rates and low-interest margins on Government Securities which is evidently reflected in the low Earning per Share and low share prices of commercial banks. To confronting this, the banks are forced to diversify their income. The past studies show the mixed inferences about the reliance on non-interest income can be profitable for commercial banks in Pakistan’s case. This research fills the gap for the existence of a non-linear relationship between the non-interest income and profitability of banks in Pakistan. Threshold Regression Model is applied on a panel data of 13 commercial for the period 2007-2017. The results have shown that optimal diversification benefit can be attained by reaching to a certain level of non-interest income proportion. The findings of the study are: (1) there exist a single threshold, confirming the non-linear relationship between the Non-Interest Income ratio (NIR) and profitability (ROE). (2) The NIR impacts positively on profitability (ROE) when NIR (≤61.1%) and beyond this value i.e. NIR (>61.12%) the relationship is negative. The study can help the Pakistani banks in exploiting their maximum level of diversification and in earning large profits in unfavorable times.